Development of Student Activity Sheets Based on Analytical Thinking Skills Managed With a Guided Inquiry Learning Model on Thermochemistry Material Containing Three Scientific Questions - Ersa Sania Azzahro'; Suyono Suyono; Maharani Agustina Arivi (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
Analytical thinking skills (ATS) are a crucial skill to master in the 21st century. Students’ low ATS in chemistry, particularly thermochemistry, requires structured material through three scientific questions and the use of appropriate learning models. This study aims to develop student activity sheets (SAS) to improve students’ ATS using a guided inquiry model on thermochemistry material that is suitable based on the aspects of validity, practicality, and effectiveness. Thermochemistry material is arranged through ontology, epistemology, and axiology questions. The type of research used is research and development with the ADDIE (analyze, design, develop, implement, evaluate) development model. Validity is measured based on the assessment of three validators, and the mode or median value obtained is in the range 4–5 in content validity and construct validity, so it is declared valid to very valid. Practicality is measured based on student responses with a percentage of 74.55% and practical criteria. Effectiveness is obtained through the pretest and posttest results. The pretest and posttest results showed an increase in all indicators, both categories (from low category to high category), scores obtained by students on each indicator, and percentage (differentiating from 52.25 to 81.82%, organizing from 25 to 84.85%, and connecting or attributing from 13.64 to 80.30%). Based on the research results, the developed SAS is suitable for use in learning